Strategies of Improving The Quality of Public Service at The Investment and Services Office Integrated One Door of Banjar City West Java Province - Soni Harison; Kamal Alamsyah (Doctoral Program of Social Science Pasundan University, 2021)
There are still people's views that think that the implementation of public services is still very slow and inefficient in responding to changes and does not adapt to changes in the development paradigm. The number of complaints submitted by the community, especially the business community in receiving public services from the government bureaucracy, among others: complicated procedures, no clarity about the time to solve problems, and no clarity about the amount of costs to be incurred, coupled with low quality of service. The method used in this study is a qualitative research method, while the type of approach in this study is descriptive analysis. Analysis of the data used is data analysis according to Miles and Hubberman with a qualitative approach. The results of the study indicate that the gap between the quality of public services and public expectations still occurs, therefore there must be improvement in service performance related to elements of service procedures, cost certainty, officer certainty, and service speed. In services that are currently considered good by the community, they are able to encourage investment activities in Banjar City, because they are able to create cheap, fast and transparent services. There has been an increase in the transparency of public services. Based on the results of the study, it can be concluded that the Banjar City DPMPTSP must continue to improve the quality of services with high commitment, consistency, and the need for legal certainty. Improving service quality needs to be accompanied by a program to simplify service procedures so as to increase the speed of service, create a conducive work environment, and strengthen institutions as providers of licensing service activities can run effectively and efficiently through strengthening information and communication technology